Social Networks and Electoral Campaigns in Latin America. a Comparative Analysis of the Cases of Spain, Mexico and Chile [Redes Sociales y Campañas Electorales en Iberoamérica. Un Análisis Comparativo de Los Casos de España, México y Chile] - Jara-Reyes, R (Pontificia Universidad Catolica de Chile, 2017)
In this article, we made a comparative analysis of the research on social networks and electoral campaigns in the Ibero-American context in three cases of study: Spain, Mexico and Chile. From a bibliographic analysis, similarities and differences were identified, contributing to the generation and consolidation of the theory regarding such a recent, and in a continuous process of change, study object, such as the technologies that have produced it. We observed a widespread implementation of the use of diverse and changing digital platforms, as well as a superficial application of the social communication tools.